Cognitive behavioral therapy for the busy child psychiatrist and other mental health professionals : rubrics and rudiments - Friedberg, Robert D., 1955- (New York : Brunner-Routledge, 2011)
'Teaching Child Psychiatrists Cognitive Behavioral Therapy is an essential resource for clinical child psychologists, psychiatrists and psychotherapists, and mental health professionals. Since 2001, psychiatry residency programs have required resident competency in five specific psychotherapies, including cognitive-behavioral therapy. This unique text is a guidebook for instructors and outlines fundamental principles, while offering creative applications of technique to ensure that residency training programs are better equipped to train their staff'--
Includes bibliographical references and index.
Keywords: Cognitive therapy for children; Cognitive therapy for teenagers; Child psychotherapy; Adolescent psychotherapy